2022
DOI: 10.1371/journal.pntd.0010716
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of invasive typhoidal and non-typhoidal Salmonella in southwestern Nigeria

Abstract: Background Salmonellosis causes significant morbidity and mortality in Africa. Information on lineages of invasive Salmonella circulating in Nigeria is sparse. Methods Salmonella enterica isolated from blood (n = 60) and cerebrospinal fluid (CSF, n = 3) between 2016 and 2020 from five tertiary hospitals in southwest Nigeria were antimicrobial susceptibility-tested and Illumina-sequenced. Genomes were analysed using publicly-available bioinformatic tools. Results Isolates and sequence types (STs) from blood… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…However, overall, bla CTX-M-15 IncY plasmids were rare (n=1 to 4 genomes) in all genotype backgrounds except 4.3.1.1.P1 (total n=655), suggesting that the IncY bla CTX-M-15 plasmid has not been stably maintained in other Typhi lineages (see Table 3). IncY plasmids were also identified in a single genotype 2.3.3 organism isolated in the UK in 1989 associated with travel to Pakistan (carrying catA1, tetA(B)); and in a sublineage of IncHI1-negative 3.1.1 genomes from Nigeria carrying bla TEM-1D , dfrA14, sul2, tetA(A), as has been recently reported (Ikhimiukor et al, 2022a;International Typhoid Consortium et al, 2016). Other examples of ESBL carriage in Typhi genomes appear to represent isolated events (1 or 2 genomes per ESBL/plasmid or ESBL/genotype combination, see Table 3), except for a sublineage of 4.3.1.2.1 from India carrying bla SHV-12 in a IncX3 plasmid backbone.…”
Section: Ceftriaxone Resistant (Cefr)supporting
confidence: 72%
See 3 more Smart Citations
“…However, overall, bla CTX-M-15 IncY plasmids were rare (n=1 to 4 genomes) in all genotype backgrounds except 4.3.1.1.P1 (total n=655), suggesting that the IncY bla CTX-M-15 plasmid has not been stably maintained in other Typhi lineages (see Table 3). IncY plasmids were also identified in a single genotype 2.3.3 organism isolated in the UK in 1989 associated with travel to Pakistan (carrying catA1, tetA(B)); and in a sublineage of IncHI1-negative 3.1.1 genomes from Nigeria carrying bla TEM-1D , dfrA14, sul2, tetA(A), as has been recently reported (Ikhimiukor et al, 2022a;International Typhoid Consortium et al, 2016). Other examples of ESBL carriage in Typhi genomes appear to represent isolated events (1 or 2 genomes per ESBL/plasmid or ESBL/genotype combination, see Table 3), except for a sublineage of 4.3.1.2.1 from India carrying bla SHV-12 in a IncX3 plasmid backbone.…”
Section: Ceftriaxone Resistant (Cefr)supporting
confidence: 72%
“…Most of these data come from the Typhoid Fever Surveillance in Africa Programme (TSAP) genomics report (Park et al, 2018) and a study of typhoid in Abuja and Kano in Nigeria (International Typhoid Consortium et al, 2016), which showed that in the period 2010-2013, 3.1.1 dominated in Nigeria and nearby Ghana and Burkina Faso, whereas 2.3.2 dominated in The Gambia and neighbouring Senegal and Guinea Bissau (Park et al, 2018). Here, we find that additional data from travel cases and recent Nigerian national surveillance (Ikhimiukor et al, 2022a) suggest that these patterns reflect long-established and persisting populations in the Western African region (see Figures S1b and S3): 3.1.1 was detected from Benin (2002Benin ( -2009n=4/4), Burkina Faso (2006-2013n=11/17), Cote d'Ivoire (2006n=4/4) -2014n=25/28), Ghana (2010n=25/28), Ghana ( -2018n=9/109), Guinea Bissau (2012-2013n=2/3), Mali (1999n=2/3), Mali ( -2018n=3/5), Niger (1990n=3/5), Niger ( -1999n=2/4), Nigeria (1984n=2/4), Nigeria ( -2002n=4/192) The Americas Strikingly, Central American isolates were dominated by 2.3.2 (55%, [95% CI, 45.2-64.8%] n= 55/100), which was also common in Western Africa (13.9%, [95% CI, 9.7-18.0%]; n=37/266) (Figure 1a). Little has been reported about Typhi populations from this region previously, and the genomes collated here were almost exclusively novel ones contributed via the US CDC and isolated between 2016 and 2019.…”
Section: Africamentioning
confidence: 52%
See 2 more Smart Citations
“…Moreover, our WGS surveillance found a sublineage of 3.1.1 strains that carry an IncY multi-drug resistance plasmid (Fig. 3) [45]. In addition to providing valuable information about Typhi epidemiology in Nigeria, genomic surveillance has made it possible to correctly subtype invasive non-typhoidal Salmonella, all of which are submitted by sentinels to the reference laboratory with no serovar information.…”
Section: Defining Transmission Patterns For Community-acquired Bacter...mentioning
confidence: 93%